2016
DOI: 10.1371/journal.pone.0164815
|View full text |Cite
|
Sign up to set email alerts
|

Collinearity Analysis and High-Density Genetic Mapping of the Wheat Powdery Mildew Resistance Gene Pm40 in PI 672538

Abstract: The wheat powdery mildew resistance gene Pm40, which is located on chromosomal arm 7BS, is effective against nearly all prevalent races of Blumeria graminis f. sp tritici (Bgt) in China and is carried by the common wheat germplasm PI 672538. A set of the F1, F2 and F2:3 populations from the cross of the resistant PI 672538 with the susceptible line L1034 were used to conduct genetic analysis of powdery mildew resistance and construct a high-density linkage map of the Pm40 gene. We constructed a high-density li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…At present, although Pm21 is still effective and the most widely applied Pm gene in the country [ 16 ], some newly emerged and virulent isolates have been reported to overcome Pm21 resistance in various regions [ 17 , 18 ]. We found that Pm40 still confers strong resistance to powdery mildew in various regions [ 2 , 19 , 20 ]. It was also effective against nearly all isolates collected from the main Chinese wheat growing regions, which indicated that Pm40 could have a large potential role in the improvement in resistance against powdery mildew in China in the future, especially in the post- Pm21 era [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…At present, although Pm21 is still effective and the most widely applied Pm gene in the country [ 16 ], some newly emerged and virulent isolates have been reported to overcome Pm21 resistance in various regions [ 17 , 18 ]. We found that Pm40 still confers strong resistance to powdery mildew in various regions [ 2 , 19 , 20 ]. It was also effective against nearly all isolates collected from the main Chinese wheat growing regions, which indicated that Pm40 could have a large potential role in the improvement in resistance against powdery mildew in China in the future, especially in the post- Pm21 era [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, we first identified PmE controlling resistance to powdery mildew in the wheat line YU25 by genetic analysis [ 38 ], which was consequently mapped to chromosome 7B and formally named Pm40 [ 19 ]. In a later study, Pm40 was further mapped to a short chromosomal region of 7BS flanked by Xwmc335 (with distances of 0.58 cm) and BF291338 (with distances of 0.26 cm) [ 20 ]. With the release of the Chinese spring reference genome sequence, it was feasible and workable to identify the effective candidate gene of Pm40 because the high-quality reference genome information was available.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resistance gene Pm40 was transferred from Elytrigia intermedium into wheat line GRY19 and mapped on chromosome arm 7BS [ 21 ]. Pm40 is flanked by Xwmc335 and BF291338 at genetic distances of 0.58 cM and 0.26 cM, respectively, in deletion bin C-7BS-1-0.27 [ 22 ]. Wheat line L699 , which is the high generation of wheat line GRY19 , carries the resistance gene Pm40 and confers resistance to all available isolates of Bgt in China [ 23 ].…”
Section: Introductionmentioning
confidence: 99%